(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Osteosarcoma is the most common malignant bone tumor of Paediatric and adolescent age. Historically radical treatments were opted but with advances in diagnosis and neoadjuvant chemotherapy limb salvage has now become possible in most of the cases. In this case report we presented an 8 year old girl who was diagnosed with osteosarcoma of the distal femur. She was treated successfully with neoadjvant chemotherapy followed by limb salvage surgery using partial resection of medial femoral cortex with lateral cortex remains in continuity and poraline silicon bone substitute for filling the defect. She is disease free after 3.5 year and walking pain free on her limb.